The Impact of Internet Slang on Informal Communication Among Bruneian Gen Z - Athiyyah Suhaini; Mas Ayu Mumin (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
This study examines the impact of internet slang on the informal communication of Gen Z in Brunei Darussalam. Using a quantitative research approach, a cross-sectional survey was administered to a total of 122 Gen Z respondents aged between 13 and 28. The survey aims to explore internet slang usage patterns, their impact on communication clarity, social identity, and sense of belonging, and to gather opinions and attitudes toward internet slang. The findings reveal that internet slang is being integrated into daily conversations, with clipping, acronyms, and abbreviations being the most common types used. The usage of slang was mainly due to its efficiency, fun & engaging nature, and its ability to express emotions better. Additionally, it helps to create shared identity between peers and helps to create a sense of belonging. However, the results also highlight some challenges, such as misunderstanding and misinterpretations. Overall, there is a mix of opinions and attitudes toward internet slang, which can be further investigated in future studies.